Tactile experience shapes prey-capture behavior in Etruscan shrews - Brecht, Michael; Anjum, Farzana (Frontiers in Behavioral Neuroscience, 2012)
A crucial role of tactile experience for the maturation of neural response properties in the somatosensory system is well established, but little is known about the role of tactile experience in the development of tactile behaviors. Here we study how tactile experience affects prey capture behavior in Etruscan shrews, Suncus etruscus. Prey capture in adult shrews is a high-speed behavior that relies on precise attacks guided by tactile Gestalt cues. We studied the role of tactile experience by three different approaches. First, we analyzed the hunting skills of young shrews right after weaning. We found that prey capture in young animals is most but not all aspects similar to that of adults. Second we performed whisker trimming for three to four weeks after birth. Such deprivation resulted in a lasting disruption of prey capture even after whisker re-growth: attacks lacked precise targeting and had a lower success rate. Third, we presented adult shrews with an entirely novel prey species, the giant cockroach. The shape of this roach is very different from the shrew’s normal (cricket) prey and the thorax – the preferred point of attack in crickets – is protected a heavy cuticle. Initially shrews attacked giant roaches the same way they attack crickets and targeted the thoracic region. With progressive experience, however, shrews adopted a new attack strategy targeting legs and underside of the roaches while avoiding other body parts. Speed and efficiency of attacks improved. These data suggest that tactile experience shapes prey capture behavior.